2017
DOI: 10.1186/s12879-017-2286-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated prevalence of multidrug-resistant gram-negative organisms in HIV positive men

Abstract: BackgroundRoutes of transmission of multidrug-resistant gram-negative organisms (MDRGN) are not completely understood. Since sexual transmission of MDRGN might represent a potential mode that has not been noticed so far, this study evaluated transmission of MDRGN in HIV positive men.MethodsBetween November 2014 and March 2016, we retrospectively investigated the MDRGN prevalence in rectal swabs of n = 109 males tested positive for HIV (HP). These findings were compared to the MDRGN prevalence in n = 109 rectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
4
1
1
Order By: Relevance
“…There are studies that showed a higher frequency of colonization by multidrug resistant bacteria in HIV patients, suggesting possible sexual transmission of these bacteria. [36] Our study did not find a difference between HIV and non-HIV patients in the colonization rate by carbapenem-resistant Enterobacteriaceae in HAI caused by MDROs.…”
Section: Discussioncontrasting
confidence: 53%
“…There are studies that showed a higher frequency of colonization by multidrug resistant bacteria in HIV patients, suggesting possible sexual transmission of these bacteria. [36] Our study did not find a difference between HIV and non-HIV patients in the colonization rate by carbapenem-resistant Enterobacteriaceae in HAI caused by MDROs.…”
Section: Discussioncontrasting
confidence: 53%
“…We designed an analytical cross-sectional study of HIV-positive (cases) and HIV-negative (controls) with one control per case. Prior research findings indicated that the prevalence of multidrug resistance amongst HIV-negative patients was 0.083 [15]. Assuming that the true prevalence rate of multidrug resistance in HIV-positive patients was 0.24, a sample size of 85 HIV-positive patients and 85 HIV-negative patients was required to reject the null hypothesis that these two proportions are equal with 0.8 power (Figure 1.)…”
Section: Sample Size Justificationmentioning
confidence: 99%
“…A reference strain of E. coli (ATCC-25922) was used as a control. Some studies define multidrug-resistant E.coli as having resistance to three families of drugs, while others define it as having resistance to cotrimoxazole, that is, having extended-spectrum beta-lactamase (ESBL) activity and resistance to third-and fourth-generation cephalosporins and fluoroquinolones with or without carbapenem resistance [15,19]. In this study, the E.coli isolates were predominantly resistant to cotrimoxazole; therefore, we defined multidrug resistance for our analysis as resistance to aminoglycosides and fluoroquinolones, which are amongst the main drugs of choice in the treatment of infection due to E. coli in this setting.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%
“…Ce défi croissant peut s'expliquer entre autres par le portage fécal, largement rapporté, des bactéries productrices de BLSE chez les patients infectés par le VIH [ 22 ], probablement due à la pression sélective liée au recours à la prophylaxie au cotrimoxazole d'une part et à la forte incidence d'infections bactériennes nécessitant une antibiothérapie chez le PVVIH d'autre part. Étant donné que les carbapénèmes sont devenus les molécules de choix contre les bactéries multirésistantes, des cas de résistance à ces molécules sont de plus en plus rapportés [ 4 , 17 ]. Dans notre observation, les Pseudomonas sp étaient les principaux (22,2%) germes résistants aux carbapénèmes.…”
Section: Discussionunclassified